2014
DOI: 10.1208/s12249-014-0160-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ascorbic Acid on the Degradation of Cyanocobalamin and Hydroxocobalamin in Aqueous Solution: A Kinetic Study

Abstract: Abstract. The degradation kinetics of 5×10−5 M cyanocobalamin (B 12 ) and hydroxocobalamin (B 12b ) in the presence of ascorbic acid (AH 2 ) was studied in the pH range of 1. , respectively, indicating a greater effect of AH 2 on B 12b compared to that of B 12 . The k obs -pH profiles for both B 12 and B 12b show the highest rates of degradation around pH 5. The degradation of B 12 and B 12b by AH 2 is affected by the catalytic effect of phosphate ions on the oxidation of AH 2 in the pH range 6.0-8.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…During subsequent storage, the vitamin B 12 form was found to be degraded by an additional 20%. In the presence of ascorbic acid, hydroxocobalamin is a known oxidation product of cyanocobalamin . However, our current method was unable to distinguish hydroxocobalamin from its unoxidized form.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…During subsequent storage, the vitamin B 12 form was found to be degraded by an additional 20%. In the presence of ascorbic acid, hydroxocobalamin is a known oxidation product of cyanocobalamin . However, our current method was unable to distinguish hydroxocobalamin from its unoxidized form.…”
Section: Resultsmentioning
confidence: 68%
“…In the presence of ascorbic acid, hydroxocobalamin is a known oxidation product of cyanocobalamin. 64 However, our current method was unable to distinguish hydroxocobalamin from its unoxidized form. As the cyanocobalamin concentration decrease is very pronounced (>60%), an impact on CDM performance is likely.…”
Section: Thiamine and Cyanocobalaminmentioning
confidence: 73%
“…A one‐electron reduction by ascorbate produces vitamin B 12r , which then yields hydroxocobalamin via oxidation by air (Gakenheimer & Feller, ; Macek, ; Reddy, ; Trenner, Buhs, Bacher, & Gakenheimer, ). Degradation by ascorbate proceeds further, and it was shown that ascorbate‐mediated degradation of hydroxocobalamin occurs at a rate about 10x that of cyanocobalamin (Ahmad et al, ). This ascorbate‐mediated degradation is enhanced in the presence of Cu 2+ salts, and cyanocobalamin can also be degraded by the reduced form of ascorbic acid and dehydroascorbic acid (Bartilucci & Poss, ; Rosenberg, ).…”
Section: Cyanocobalaminmentioning
confidence: 99%
“…Ascorbate promoted the degradation of B 12 in the solution. Ahmad et al ( Ahmad et al, 2017/01 ), ( Ahmadet aleng, 2014 ) described the degradation product as hydroxocobalamin, which is further rapidly degraded to products that do not elicit the vitamin functions. The degradation of cyanocobalamin to hydroxocobalamin involves the loss of the CN-group.…”
Section: Discussionmentioning
confidence: 99%